Pendampingan Pengolahan Metode Basah Di LMDH Argo Santoso, Desa Curapoh, Kecamatan Curahdami, Bondowoso - Muhammad Ghufron Rosyady Rosyady; Ketut Anom Wijaya; Sholeh Avivi; Bambang Kusmanadhi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Coffee productivity in the village of Curah poh is low. Based on the data we have obtained from discussions with the Village Head of Curahpoh, coffee productivity is around ± 300 ku/ha. This is due to several things, namely unclear coffee varieties, not optimal coffee care and poor harvest and post-harvest handling. Improper harvest and post-harvest handling will damage the coffee product, reducing its quality and quantity. Farmers currently only carry out dry method processing. Processing Wet Method will bring out the distinctive taste of coffee. The distinctive taste of coffee arises from the fermentation process in the wet method. Escort and mentoring of wet method processing needs to be done because there are several stages in the process. The conclusions that can be drawn from several service activities that have been carried out are: Coffee farmers have been able to process coffee with wet, honey and natural methods; and the coffee farmers of Curahpoh are committed to processing coffee using the wet or honey method if the market can appreciate the processed coffee beans at a good price. In 2022, it is hoped that OCE coffee beans can be roasted and powdered and packaged properly